MENINGKATKAN KEMAMPUAN MENGENAL KONSONAN BILABIAL PADA KATA BENDA DENGAN MENGGUNAKAN MEDIA POWER POINT BAGI ANAK AUTIS - Mariatul, Zulmiyetri, Irdamurni (Universitas Negeri Padang, 2013)
The research problem is motivated by an autistic child (x) in the class 1C1 SLB Lintau Buo, where the child always eliminate consonants b, m, p every word read. The facts show that the child has problems in recognizing consonants b, m, p. Therefore, researchers choose power point media to reduce omission b, m, p in children. The study was a single subject design research with ABA. Results of data analysis showed that during the study period of 30 days seems to improvements in children's ability of stable baseline only 2 words to increase to 24 words after being given intervention. This proves the provision of media power point positive impact in reducing omission b, m, p for autistic class Bhayangkari Linta Buo 1CI SLB. From these results it can be concluded that the provision of power point media can reduce omission on nouns for autistic (x)